Boosting the Adult EFL literacy in Indonesian context: Revisiting the Universality of Schema Theory - Nasmilah (EDUVELOP, 2022)
This study explores the interplay of adult EFL learners’ reading ability and the universality of schema theory. The conceptual relationship between the two aspects are discussed in an attempt to provide better understanding of why this study is essential for Second Language Acquisition (SLA) audience, both the practitioners and the researchers. Content-based Instruction (CBI) and Traditional Instruction (TI) materials are applied to six groups of ESP (English for Specific Purposes) adult learners comprising Agriculture, Engineering and Economic classes which accommodate 25-27 students each. Utilizing classroom observation, the study reveals detail interactions which occur during the teaching and learning processes. The activation of schemata or background knowledge during the process of learning, specifically, reading skills is clearly shown in the CBI classes while such cognitive process does not seem to occur in the implementation of Traditional Instruction (TI) material. This leaves a substantial recommendation for future researchers and practitioners of SLA to incorporate schema theory in whatever design they are pursuing in relation to developing teaching instructions for Reading skills.